Recovery with distress: Unpacking COVID-19 impact on livelihoods and poverty in Bangladesh - Rahman, Hossain Zillur; Rahman, Atiya; Islam, Md. Saiful; Faruk, Avinno; Matin, Imran; Wazed, Mohammad Abdul; Zillur, Umama (United Nations University World Institute for Development Economics Research, 2024)
The social and economic impact of COVID-19 has been deep, wide-ranging, and multi dimensional. While anecdotal evidence of distress among the poor, particularly those with informal occupations, has been widespread, effective policy response has required real-time, researched data disaggregated for urban and rural populations and for various categories of the poor. The Power and Participation Research Centre and BRAC Institute of Governance and Development’s four round panel survey during 2020–21 provides unique insights into how COVID-19 impacted specific categories of the poor and vulnerable in Bangladesh, their coping strategies, and the extent to which policy support materialized. While the poor as a whole demonstrated their agency in the face of the crisis, their resilience has been as much about deepening vulnerability as about recovery, representing an unfair burden of distress resilience. Informal workers, women, and the urban poor have been disproportionately impacted.